1997
DOI: 10.1016/s0006-3495(97)78344-9
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the efficiency of G protein activation by ligand-free and light-activated forms of rhodopsin

Abstract: Activation of the photoreceptor G protein transducin (Gt) by opsin, the ligand-free form of rhodopsin, was measured using rod outer segment membranes with densities of opsin and Gt similar to those found in rod cells. When GTPgammaS was used as the activating nucleotide, opsin catalyzed transducin activation with an exponential time course with a rate constant k(act) on the order of 2 x 10(-3)s(-1). Comparison under these conditions to activation by flash-generated metarhodopsin II (MII) revealed that opsin- a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
85
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(91 citation statements)
references
References 53 publications
6
85
0
Order By: Relevance
“…Changes in the morphology of the LratϪ/Ϫ retina are small, as evidenced by slight shortening of ROS at early age (6 -8 weeks). This abnormality may result from the constitutive activity of opsin because steady-state activation of phototransduction by the receptor (42)(43)(44) was also proposed as a cause of retinal degeneration in Rpe65Ϫ/Ϫ mice (28,45). Similar observations were made for Rpe65Ϫ/Ϫ mice which also contain large amount of opsin, reduced length of ROS, but minute amounts of active visual pigments (28,46).…”
Section: Discussionmentioning
confidence: 64%
“…Changes in the morphology of the LratϪ/Ϫ retina are small, as evidenced by slight shortening of ROS at early age (6 -8 weeks). This abnormality may result from the constitutive activity of opsin because steady-state activation of phototransduction by the receptor (42)(43)(44) was also proposed as a cause of retinal degeneration in Rpe65Ϫ/Ϫ mice (28,45). Similar observations were made for Rpe65Ϫ/Ϫ mice which also contain large amount of opsin, reduced length of ROS, but minute amounts of active visual pigments (28,46).…”
Section: Discussionmentioning
confidence: 64%
“…Opsin has a low activity towards the G protein [84,85,86,87], but the activity is enhanced by several orders of magnitude when all-trans-retinal is present to form a non-covalent complex with opsin [88,89,90]. By infrared spectroscopy in vitro on disk membranes it was shown that opsin exists in a pH-dependent equilibrium of two conformations with a pK a of 4.1 at 30 °C…”
Section: ____________________________________________________________mentioning
confidence: 99%
“…B) Superposition of rhodopsin (green; [47]), photoactivated rhodopsin (yellow; retinal not resolved; [68]) and opsin (orange; [120] Surface models of A) rhodopsin [47] and B) opsin [120]. [81,87]. However, in the native membrane, low pH can force proton uptake by opsin and thus formation of a state which shows a FTIR spectroscopic signature that is comparable to active Meta II [91].…”
Section: Alterations In the Retinal Binding Sitementioning
confidence: 99%
“…Our experiments demonstrated that opsin even without chromophore is noisy, occasionally triggering the activation of transducin (32) and collectively producing an electrical response; these observations were later confirmed by biochemical measurement of opsin activity. (33) The rate of activation is exceedingly small: in salamander it takes 10 6 -10 7 opsin molecules to have the effect of a single light-activated rhodopsin per second. Mammalian opsin is considerably noisier, though it still takes of the order of 10 4 -10 5 opsin molecules to have the effect of one Rh* per second.…”
Section: Continuous Light Kills By Activating Transductionmentioning
confidence: 99%